Pelatihan Serta Pendidikan di Bapqah Sika Sumatera Utara terhadap Kajian Hafiz Hafizah, Qari-qari’ah dan Kaligrafi - Sulaiman Muhammad Amir; Balqis Nur Afifah; Gustina Zulfiani Sitorus; Lauh Mahfuzh Fahrozy; Miftahul Jannah; Muas Fadil; Nur Izzati Afifah (Jurnal Budi Pekerti Agama Islam, 2024)
The study used a qualitative methodology and collected data from various sources by means of interviews, observations and analyzing related documents. The aim is to evaluate the institutions established by BAPQAH SIKA North Sumatra, namely education and training for Calligraphy, Hafiz-hafizhah and Qari-qariah. With this data collection method, it was found that routine education and training was carried out, except on Saturday nights, at no cost. However, educational management is not yet fully professional, especially in a curriculum that is not yet clearly structured. In the teaching and learning process, various methods such as demonstration, muthala'ah, qiraat, Wahdah for tahfiz, and assignments for Arabic calligraphy are applied. Despite facing limited financial resources which make it difficult to recruit professional teachers, education and training continues to run effectively. Students who excel in the MTQ event demonstrate the quality of education provided, even though most of the teachers are students who are experienced and have excelled in the same event.